2006
DOI: 10.2139/ssrn.1303013
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Boomers Plan to Work so Long?

Abstract: The Center for Retirement Research at Boston College, part of a consortium that includes parallel centers at the University of Michigan and the National Bureau of Economic Research, was established in 1998 through a grant from the Social Security Administration. The goals of the Center are to promote research on retirement issues, to transmit new findings to the policy community and the public, to help train new scholars, and to broaden access to valuable data sources. Through these initiatives, the Center hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…33. A recent study (Mermin, Johnson and Murphy 2006), using the Health and Retirement Study, reported a signifi cant 4 percentage point increase between 1992 and 2004 in the expected probability among workers aged 51 to 56 years staying employed full-time past age 62, from 47 to 51 percent, and a similar increase in the probability of staying employed full-time past 65, from 27 to 33 percent. Controlling for other factors, self-employment, more education, and previous higher earnings increased work expectations, while defi ned benefi t pension coverage, employer-sponsored retiree health benefi ts, and household wealth reduced expectations that older adults would remain in the workforce.…”
Section: Some Researchers (Seementioning
confidence: 98%
“…33. A recent study (Mermin, Johnson and Murphy 2006), using the Health and Retirement Study, reported a signifi cant 4 percentage point increase between 1992 and 2004 in the expected probability among workers aged 51 to 56 years staying employed full-time past age 62, from 47 to 51 percent, and a similar increase in the probability of staying employed full-time past 65, from 27 to 33 percent. Controlling for other factors, self-employment, more education, and previous higher earnings increased work expectations, while defi ned benefi t pension coverage, employer-sponsored retiree health benefi ts, and household wealth reduced expectations that older adults would remain in the workforce.…”
Section: Some Researchers (Seementioning
confidence: 98%
“…Members of the Baby Boomer generation are likely to remain in the workforce longer than previous generations, are more resistant to layoffs, and are often preferred by employers due to their knowledge, skills and work ethic (Mermin et al 2008). According to Yang and DeVaney (2011), individuals who reported that they would continue to work even if they did not need the money were more likely to engage in retirement planning activities, and thus, these consumers are also likely to continue to access credit and investment markets.…”
Section: Aging In the Marketplacementioning
confidence: 99%
“…According to Yang and DeVaney (2011), individuals who reported that they would continue to work even if they did not need the money were more likely to engage in retirement planning activities, and thus, these consumers are also likely to continue to access credit and investment markets. However, once unemployed, these older individuals remain out‐of‐work, on average, longer than their counterparts (Mermin, Johnson, and Toder 2008). According to Vanguard, hardship withdrawals from 401K plans increased by 49% between 2005 and 2010.…”
Section: Aging In the Marketplacementioning
confidence: 99%
“…Comparing the results of studies over time is complicated, as the average age of male retirement fell steadily for most of the last century, though the decline leveled out over the last 20 years. Mermin, Johnson, and Murphy (2006) report that the mean expected probability of full-time work after age 65 grew to 33 percent (from 27 percent) among workers age 51 to 56 between 1992 and 2004. They attribute the changes primarily to the declining generosity (and increasing cost) of retiree health insurance, increase in educational attainment (which results in less physically demanding and less tedious jobs), and lower defined-benefit pension coverage (and the associated strong retirement incentives found in DB plans).…”
Section: Introductionmentioning
confidence: 99%